Structural policy indicators database for economic research (SPIDER) - Égert, Balázs (OECD Economics Department Working Papers, 2017)
This document describes the OECD's new Structural Policy Indicators Database for Economic Research (SPIDER). The database compiles data from various existing databases. It contains indicators capturing structural policies (including institutions, framework condition policies and policies specifically related to labour markets and drivers of productivity and investment such as trade, skills and innovation). It also contains some basic macroeconomic indicators. The main idea of the database is to provide all the data needed for empirical analysis on structural policies in one place to facilitate empirical investigations. The indicators collected comprise three types of data: data with long-time series covering OECD countries, data covering a larger set of countries for a varying number of years, and finally a set of time-invariant indicators. The paper illustrates the use of the database on the basis of different growth regressions employed in the literature